Investigation for methods of anesthesia and euthanasia for rat fetuses in developmental toxicity studies. (11th March 2013) - Kato, Hirohito; Dokai, Momoko; Katagiri, Ryuichi; Arima, Akihiro; Ooshima, Yojiro
Abstract Japan Association for Laboratory Animal Medicine (JALAM) recommends humane handling of rat fetuses. However, it is a challenge to accept proposed euthanizing methods such as cervical dislocation, decapitation and/or intracardiac injection of potassium chloride, because these methods would damage fetal specimens for skeletal and visceral examinations in developmental toxicity studies. The present study aimed at seeking better methodologies for fetal euthanasia and anesthesia. We were unable to accomplish fetal euthanasia directly, but instead, we could euthanize fetuses under pain‐controlled anesthesia. It is recommended that hypothermia by immersion in cold physiological saline is an appropriate method for anesthesia. Moreover, we recommend that the anesthetized fetuses should be euthanized immediately by removal of the vital organs or immersion in appropriate fixatives.